QUAN TRẮC dl-PCB THEO MÙA BẰNG THIẾT BỊ LẤY MẪU KHÔNG KHÍ THỤ ĐỘNG VỚI PHIN LỌC PUF - Trịnh, Khắc Sáu; Nguyễn, Thị Thu; Nguyễn, Thị Dung (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEASONAL MONITORING OF dl-PCBs BY USING THE PASSIVE AIR SAMPLER WITH PUF FILTERWe have carried out seasonal monitoring of twelve congeners of dioxin like-PCB (dl-PCB) in urban ambient air in Hanoi using passive air sampler with polyurethane foam (PUF) filter. 13C-labeled dl-PCB surrogate standards have been added on the PUF filters at the beginning of sampling to evaluate the efficiency of dl-PCB retention during the monitoring period. Most of 13C-labeled dl-PCBs are stable and well maintained on the PUF filters in all seasons. In general, the efficiency of their retention ranged from 27.2% to 190%. The concentration of native dl-PCB congeners, which found on PUF filters with or without 13C-labeled dl-PCBs in different seasons have a coefficient of variance ≤ 35%. It means that this sampling method has good replication. Profile of dl-PCBs in ambient air in the study area has been determinated. PCB#118 always has the highest concentration from 15.3 to 62.4 pg/filter/day. Total TEQdl-PCBs highest is 0.063 pg/filter/day in winter of 2013. The results indicated that seasonal monitoring of dl-PCBs may be carried out by using passive air sampler with PUF filter in the tropical climate in Northern Vietnam.